Influencia de la construcción de la Represa en la Protección Hidrológica de la Microcuenca Río Grande - Andrade Vélez, Wilter Romario (2018)
The relationship between the hydrological protection and the vegetation cover of the sub-basin of the Carrizal river was determined by calculating the Hydrological Protection Index (HPI). For this, information was collected about the activities carried out in the Chone Multiple Purpose project to evaluate the influence of the activities on the environmental components through the Buroz methodology. It established 28 sampling points based on the plant units that make up the micro-basin in the years 2008 and 2015. At each point transepts were developed. Finally, the methodology established by Rojas (2004) was used to calculate the Hydrological Protection Index. According to the Buroz analysis, the activity that generated high impacts on the greatest number of components was the agroforestry development of buffer zones. It should be noted that this activity was not carried out by the construction personnel. In the micro basin of Rio Grande there are 9 types of vegetation cover according to the information obtained from the National Information System, when comparing the HPI (0,649) of Río Grande micro basin before the construction of the dam (2008) with the IPH (0.549) after its construction (2015), it can be observed that there is variation between the hydrological protection indexes presenting a regular condition, which allowed concluding that it possesses a protection capacity without the need of implementing measures of plant regeneration.